2020
DOI: 10.3390/ijerph17010332
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires’ Disease Cases at a Large Community Hospital—Common and Underdiagnosed

Abstract: Legionnaires’ disease (LD) is a severe pneumonia with a mortality rate of about 10%. The illness remains largely underdiagnosed with outbreaks occurring with alarming incidence. In this study, we assessed the frequency of Legionnaires’ disease among pneumonia cases treated at a large community hospital over a summer season. We invited all admitted patients diagnosed with pneumonia, able to provide a urine sample for an antigen test, presenting from May to October 2018, to enroll in our study; 35 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…L. pneumophila outbreaks found to be from cooling tower sources have resulted in increased vigilance maintenance and control of existing cooling systems ( Nguyen et al, 2006 ; Ulleryd et al, 2012 ). Legionnaires’ disease cases often remain largely underdiagnosed with outbreaks not properly determined, due to the pneumonia-like symptoms mimicking other ailments, and lack of testing ( Spiegelman et al, 2020 ). In addition, while many biocides are available for water treatment and Legionella prevention, environmental aspects including other biota ( Orrison et al, 1983 ; McNealy et al, 2002 ), water chemistry ( Kim et al, 2002 ), and environmental factors can influence its survival and recalcitrance to biocides ( Mallison, 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…L. pneumophila outbreaks found to be from cooling tower sources have resulted in increased vigilance maintenance and control of existing cooling systems ( Nguyen et al, 2006 ; Ulleryd et al, 2012 ). Legionnaires’ disease cases often remain largely underdiagnosed with outbreaks not properly determined, due to the pneumonia-like symptoms mimicking other ailments, and lack of testing ( Spiegelman et al, 2020 ). In addition, while many biocides are available for water treatment and Legionella prevention, environmental aspects including other biota ( Orrison et al, 1983 ; McNealy et al, 2002 ), water chemistry ( Kim et al, 2002 ), and environmental factors can influence its survival and recalcitrance to biocides ( Mallison, 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most susceptible hosts of hospital-acquired Legionella pneumonia are immunocompromised patients, including organ transplant recipients (8) and cancer patients (9), as well as those receiving glucocorticoid therapy. Multiple studies have shown Legionella infections to be underdiagnosed and undertreated (1,10,11). In this case report, the patient was fortunate to be treated in time and was discharged from the hospital in good health.…”
Section: Discussionmentioning
confidence: 80%
“…Another published review article of respiratory tract infection during Hajj identified these infections as the most common cause of hospital admissions (Mandourah et al, 2012). Interestingly, a published study of formerly collected data, showed both water samples from different sources include water coolers, sprinkles, and storage tanks in Makah areas such as Arafat, Mona, Muzdaliphah, and nearby the Holy Mosque "Haram", and clinical specimens from pneumonia diagnosed patients admitted to five tertiary hospitals in Makkah and the findings showed that pneumonia was the major cause of sickness in pilgrims and recommended with more studies on water sources (Sreenath et al, 2020;Al-Tawfiq et al, 2013Spiegelman et al, 2020;Zahran et al, 2018). Absence of documented data on the isolation rates of this type of bacteria cause this disease in Saudi Arabia and in view of the results of previous studies during the Hajj season; the reason for the emergence of this type of bacteria may be due to the fact that these hotels use water from wells which can be the main source of these pathogenic bacterial strains.…”
Section: Resultsmentioning
confidence: 99%